The Politics of Capital Markets Union - Wolf-Georg Ringe (University of Hamburg, Institute of Law and Economics (ILE), 2019)
EU policymakers are currently implementing the capital markets union (CMU) agenda-a collection of individual steps that, taken together, should strengthen cross-border market integration in EU capital markets. However, the imminent departure of the United Kingdom from the EU reshuffles the cards in this project, since the absence of the United Kingdom as the continent's most developed capital market jeopardizes the objective of creating a truly Europe-wide deep and liquid market that merits its name. This paper argues that the purpose of the CMU project can and should be redefined. The initial thrust behind the project in 2014-2015 seems to have been to court the British public in a bid to influence the Brexit referendum. After the UK's vote to leave, that objective no longer provides the glue that holds the CMU agenda together. Instead, I show that CMU can helpfully be redefined and reexplained in an entirely new context. Specifically, the CMU agenda provides a sensible set of measures to strengthen the architecture of the Eurozone: cross-border integration of national financial markets holds the promise of promoting so-called 'private risk sharing' that can serve as an important boost to reinforce the fragile framework of the common currency. This paper makes two points. First, it explores the initial motivation behind launching the CMU agenda. The paper argues that the initial purpose was - among other things - a political bid to influence the growing anti-EU attitude and to win over the City of London. Since this strategy was ultimately unsuccessful - at least, it did not suffice to secure a majority voting for a UK-wide 'remain' vote - the entirety of the CMU project was put into question. In a second step, the paper shows that the CMU agenda currently on the table - if sufficiently reinforced and expanded - may find a new purpose in strengthening the Eurozone architecture. The latter point comes amid the ongoing policy debate on the future of the Euro.
Keywords: 330